The Impact of Social Media on Individual's Attitudes and Perceptions in Davao City, Philippines - Grenien, Daniel Suarez; Campos, Karl (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2023)
Social media and digital marketing are increasingly being used as a strategic tool for increasing brand awareness and running marketing campaigns. Moving away from the era of traditional or mass media, marketers can track brand competitors and have more measurable campaign results by using social media and digital marketing. Consumer behavior require businesses to craft marketing tactics in this social media driven era. This study seeks to examine how social media affects consumer views toward social media marketing and how they behave when making purchases. A survey was administered to 122 participants at Davao City looking at the perspective of the respondents toward social media marketing. The results of the study showed that social media marketing has the potential to drive the revenue of businesses. Moreover, the conduct of the study was able to identify that customers perception towards social media marketing factors has a significant effect in their purchases.